An Investigation into the use of OpenGL as a library for the simulation of infrared scenarios - Leuschner, F.W. (Friedrich Wilhelm) (University of Pretoria, 2013)
Dissertation (MEng (Electronic Engineering))--University of Pretoria, 2006.